Cancer risks in carriers of the BRCA1/2 Ashkenazi founder mutations - Kadouri, Luna (BMJ Group, 2007)
BACKGROUND: The risks for cancers other than breast (BC) or ovarian (OC) cancer in breast cancer gene 1 and 2 (BRCA1/2) mutation carriers were elevated in studies of carrier families. However, case–control studies did not confirm this observation. OBJECTIVE: To compare the risks for other cancers in BRCA1/2 mutation carriers and non‐carriers, all affected with BC and/or OC. Both groups share risk modifiers of BC/OC, which enabled assessment of the role of BRCA1/2 mutations. METHODS: 1098 Ashkenazi Jewish women affected with BC and/or OC were ascertained during 1995–2003; molecular testing revealed 229 BRCA1 and 100 BRCA2 carriers and 769 non‐carriers. COX proportional hazard models were used to evaluate the risk of other cancers. Analyses were conducted including all other cancers or only those diagnosed after BC/OC diagnosis. RESULTS: The HRs for any other cancer were 2.6 (95% CI 1.7 to 4.2, p<0.001) and 1.8 (95% CI 0.95 to 3.6, p = 0.07) in BRCA1 and BRCA2 carriers, respectively. The corresponding colon cancer HRs were 3.9 (95% CI 1.3 to 12.1, p = 0.02) and 2.3 (95% CI 0.5 to 11.3, p = 0.3) in BRCA1 and BRCA2 carriers. The HR for lymphoma was 11.9 (95% CI 3.1 to 46.2, p = 0.001) in BRCA2 carriers. Risk estimates for other cancers after the onset of BC/OC were similar. CONCLUSION: A 2.5‐fold increase in any other cancer and a fourfold risk of colon cancer were found among BRCA1 carriers. The corresponding HRs in BRCA2 carriers were non‐significant, except for the markedly elevated risk of lymphoma. These results suggest a role for BRCA1/2 mutations in colorectal cancer risk in a subgroup of BC/OC‐affected carriers.